Use of mesenchymal stem cells to treat liver fibrosis: Current situation and future prospects - Berardis, Silvia (World J Gastroenterol, 2015)
Progressive liver fibrosis is a major health issue for which no effective treatment is available, leading to cirrhosis and orthotopic liver transplantation. However, organ shortage is a reality. Hence, there is an urgent need to find alternative therapeutic strategies. Cell-based therapy using mesenchymal stem cells (MSCs) may represent an attractive therapeutic option, based on their immunomodulatory properties, their potential to differentiate into hepatocytes, allowing the replacement of damaged hepatocytes, their potential to promote residual hepatocytes regeneration and their capacity to inhibit hepatic stellate cell activation or induce their apoptosis, particularly via paracrine mechanisms. The current review will highlight recent findings regarding the input of MSC-based therapy for the treatment of liver fibrosis, from in vitro studies to pre-clinical and clinical trials. Several studies have shown the ability of MSCs to reduce liver fibrosis and improve liver function. However, despite these promising results, some limitations need to be considered. Future prospects will also be discussed in this review.